2006
DOI: 10.1002/mawe.200500971
|View full text |Cite
|
Sign up to set email alerts
|

Transformation plasticity at different phase transformations of bearing steel

Abstract: Simulation of heat treatment processes presupposes that material data exist for the description of the phase transformation. During the heat treatment transformation and thermally caused stresses develop, which affect the behaviour of the phase transformation. The subject of this paper is the interaction between phase transformation and internal stress. The investigations show the influence of constant tensile loading on transformation strains occurring during the isothermal pearlitic and bainitic transformati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…The change from linear to non-linear behavior was observed for both tensile and compressive stresses ( Figure 6), whereas the TP magnitudes were higher for tensile stresses. This asymmetric behavior has been observed earlier for bainitic and martensitic reactions [15,40], and it has been shown that the degree of anisotropy increased upon increasing the carbon amount dissolved in austenite. For the martensitic transformations, this behavior was attributed to a change in martensite morphology upon increasing the carbon content.…”
Section: Resultssupporting
confidence: 80%
“…The change from linear to non-linear behavior was observed for both tensile and compressive stresses ( Figure 6), whereas the TP magnitudes were higher for tensile stresses. This asymmetric behavior has been observed earlier for bainitic and martensitic reactions [15,40], and it has been shown that the degree of anisotropy increased upon increasing the carbon amount dissolved in austenite. For the martensitic transformations, this behavior was attributed to a change in martensite morphology upon increasing the carbon content.…”
Section: Resultssupporting
confidence: 80%
“…[20,24,25,[31][32][33] However, during forging the heating and cooling rates can be extremely high, which necessitates the availability of transformation kinetics data for various temperature-time paths. In order to shed light on the effect of austenitization temperature and time on the isothermal phase transformation kinetics, two different heat treatments were considered in the current work: a conventional heat treatment based on available time-temperature-transformation diagrams [1] and one derived from an actual forging process.…”
Section: Introductionmentioning
confidence: 99%
“…For TRIP during martensitic transformation for 100Cr6 we refer to [25,32,26]. Different values for j under tension (labelled by j + ) and compression (j -), respectively, have been reported.…”
Section: Transformation-induced Plasticity (Trip)mentioning
confidence: 98%